This is all I choose to tell : history and hybridity in Vietnamese American literature - Pelaud, Isabelle Thuy, 1965- (Asian American history and culture., 2011)
In the first book-length study of Vietnamese American literature, Isabelle Thuy Pelaud probes the complexities of Vietnamese American identity and politics. She provides an analytical introduction to the literature, showing how generational differences play out in genre and text. In addition, she asks, can the term Vietnamese American be disassociated from representations of the war without erasing its legacy?Pelaud delineates the historical, social, and cultural terrains of the writing as well as the critical receptions and responses to them. She moves beyond the common focus on the Vietnam w.